Palatal sclerotherapy for the treatment of intermittent dorsal displacement of the soft palate in 51 standardbred racehorses - Jean, Daniel (Canadian Veterinary Medical Association, 2011)
This retrospective study evaluated the efficacy and side effects of palatal sclerotherapy in standardbred racehorses suspected to have intermittent dorsal displacement of the soft palate (IDDSP). Fifty-one horses were treated with multiple endoscopically guided injections of 3% sodium tetradecyl sulfate in the soft palate. Two groups were identified: those that had respiratory noises during exercise (n = 27) and those that did not (n = 24). Treatment was well-tolerated. Furthermore, horses significantly reduced their racing times for the last 400 m compared with their times before treatment and even when their times were compared to the mean times for horses in the same race. In conclusion, palatal sclerotherapy appears to be a suitable alternative therapeutic option for horses suspected to have IDDSP.